Optimal Sizing of Battery Energy Storage Systems for Renewable Energy Integration in Energy Communities - Minetti, Manuela; Bonfiglio, Andrea; Procopio, Renato; Petronijevic, Milutin P.; Radonjic, Ivana (2024 11th International Conference on Electrical, Electronic and Computing Engineering (IcETRAN), 2024)
The integration of renewable energy sources (RESs) into electrical grids has experienced significant growth in recent decades, propelled by the pursuit of a sustainable energy future. However, as the share of renewable electricity production rises, the likelihood of overloading network components and having overvoltages also increases. Battery Energy Storage Systems (BESSs) offer a promising solution for mitigating RESs curtailment. Therefore, this paper proposes an energy storage sizing strategy aimed at minimizing RESs curtailment in a distribution system with renewable energy communities (RECs). This approach, which leverages linear voltage drop relations, distinguishes itself for its simplicity. The constraints of the optimization problem are defined to prevent overload of the primary substation transformer, issues of undervoltage and overvoltage at network nodes, and overcurrent problems in the feeders. Simulation results on a test distribution network validate the proposed method, providing a practical approach to sizing BESSs in RECs and maximizing renewable energy utilization.